2001
DOI: 10.4049/jimmunol.166.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Negative-Feedback Regulation of CD28 Costimulation by a Novel Mitogen-Activated Protein Kinase Phosphatase, MKP6

Abstract: TCR and CD28 costimulatory receptor-cooperative induction of T cell IL-2 secretion is dependent upon activation of mitogen-activated protein (MAP) kinases. Using yeast-hybrid technology, we cloned a novel CD28 cytoplasmic tail (CD28 CYT) interacting protein, MAP kinase phosphatase-6 (MKP6), which we demonstrate inactivates MAP kinases. Several lines of evidence indicate that MKP6 plays an important functional role in CD28 costimulatory signaling. First, in human peripheral blood T cells (PBT), expression of MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 57 publications
(44 reference statements)
3
85
0
Order By: Relevance
“…MKPL (MKP6) is a dual-specific MAPK phosphatase that dephosphorylates JNKs as well as ERKs and p38 MAPKs. 35 RNase protection confirmed that reducing ZBP-89 mRNA levels with ZBP-89-specific siRNA upregulates MKP6, while overexpression of ZBP-89 slightly downregulated the expression of this phosphatase (Figure 8b). Considering the kinetics of protein kinase cascades, minor changes in the activity of upstream MKP6 would cause a significant change in the phosphorylation status of the downstream JNK.…”
Section: Zbp-89 Represses Jnk Dephosphorylationmentioning
confidence: 69%
See 1 more Smart Citation
“…MKPL (MKP6) is a dual-specific MAPK phosphatase that dephosphorylates JNKs as well as ERKs and p38 MAPKs. 35 RNase protection confirmed that reducing ZBP-89 mRNA levels with ZBP-89-specific siRNA upregulates MKP6, while overexpression of ZBP-89 slightly downregulated the expression of this phosphatase (Figure 8b). Considering the kinetics of protein kinase cascades, minor changes in the activity of upstream MKP6 would cause a significant change in the phosphorylation status of the downstream JNK.…”
Section: Zbp-89 Represses Jnk Dephosphorylationmentioning
confidence: 69%
“…67 Ad-GFP (GFP: green fluorescence protein) and Ad-dnJNK2 (encoding an HA-tagged dominant-negative JNK2 mutant) Ads 68 and the Flag-MKP6-expressing retroviral vector have been described before. 35 …”
Section: Adenovirus and Retrovirusesmentioning
confidence: 99%
“…Also, DUSP14-deficient mice are more susceptible to EAE induction. A previous report (5) showed that DUSP14 interacts with CD28 in overexpressing systems. Primary human peripheral blood T cells transduced with a dominant-negative DUSP14 mutant secrete more IL-2 in response to anti-CD3 plus anti-CD28 costimulation but not anti-CD3 alone or PMA plus ionomycin.…”
Section: Discussionmentioning
confidence: 91%
“…DUSP14 (also known as MKP6) is an atypical DUSP; DUSP14 contains the consensus C-terminal catalytic domain but lacks the N-terminal CH2 domain. DUSP14 dephosphorylates JNK, ERK, and p38 in vitro (5); however, dominant-negative DUSP14 mutant enhances the activation of JNK and ERK, but not of p38, in the overexpressing system (5). DUSP14 dominant-negative mutant enhances pancreatic b cell proliferation by increasing ERK activation in the overexpressing system (6).…”
mentioning
confidence: 99%
“…CD28 engagement induces massive IL-2 secretion, which is dependent upon the activation of mitogen-activated protein (MAP) kinase (19,38). Using yeast-hybrid technique, a novel CD28 cytoplasmic tail (CD28 CYT) interacting protein, the MAP kinase phosphatase-6 (MKP6) was isolated, which showed to inactivate MAP kinases, so it is associated with cytokine secretion (39). Besides MKP6 protein, the YMNM motif on the CD28 cytoplasmic domain is also known as a binding site for PI3K and growth factor receptor-bound protein 2 (Grb-2) hence is considered to be important for CD28-induced IL-2 secretion (40,41).…”
Section: Intracellular Signals Of Costimulation In T Cell Responsementioning
confidence: 99%